2008
DOI: 10.1007/978-0-387-69080-3_28
|View full text |Cite
|
Sign up to set email alerts
|

Is the Mannose-6-Phosphate/Insulin-Like Growth Factor 2 Receptor Coded by a Breast Cancer Suppressor Gene?

Abstract: The multifunctional growth factor mannose-6-phosphate/insulin-like growth factor 2 receptor (M6P/IGF2-R) binds proteins sharing M6P signals, including cathepsins and IGF2. It is involved in targeting newly synthesized mannose-6-phosphorylated lysosomal enzymes, activating transforming growth factor beta (TGFbeta), and neutralising the mitogen IGF2 by transporting it to lysosomes. The M6P/IGF2-R was proposed as being coded by a tumor suppressor gene. We measured gene expression at the protein level by quantitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Studies at the protein level in mammary cancer showed that M6P/IGF2-R levels were significantly lower in cancer cells than in normal cells in 50% of tumors in which the peritumoral normal glands could be quantified in parallel, agreeing the hypothesis of a tumor suppressor gene for the M6P/IGF2-R [76]. Most of further studies led on M6P/IGF2-R suggested M6P/IGF2-R as being coded by a tumor suppressor gene [72,77,78] and its role as a putative prognostic marker in breast cancers has been hypothesized [76].…”
Section: Role In Human Cancersmentioning
confidence: 71%
“…Studies at the protein level in mammary cancer showed that M6P/IGF2-R levels were significantly lower in cancer cells than in normal cells in 50% of tumors in which the peritumoral normal glands could be quantified in parallel, agreeing the hypothesis of a tumor suppressor gene for the M6P/IGF2-R [76]. Most of further studies led on M6P/IGF2-R suggested M6P/IGF2-R as being coded by a tumor suppressor gene [72,77,78] and its role as a putative prognostic marker in breast cancers has been hypothesized [76].…”
Section: Role In Human Cancersmentioning
confidence: 71%
“…Some studies have speculated that M6P/IGF2-R, although characterized by a single-spanning structure, might initiate signaling cascades through G-proteins in a direct or indirect manner. It is well known that the pertussis toxin exerts its activity by binding and blocking the activation of the α subunit of the Gq/11-protein [39]. El-Shewy et al showed that the use of this toxin is able to inhibit the function of M6P/IGF2-R, therefore suggesting the involvement of G-proteins in the downstream pathway of M6P/IGF2-R. Pre-treatment of Human embryonic kidney 293 cells (HEK-293) cells with the pertussis toxin can significantly reduce the level of extracellular signal-regulated kinase 1/2 (ERK1/2) phosphorylation resulting from the interaction of IGFs with their receptors.…”
Section: Igf2r-dependent Pathwaymentioning
confidence: 99%
“…Therefore, the M6P/IGF2-R has been hypothesized as being coded by a breast cancer suppres sor gene [23], and its potential prognostic significance in breast cancer has been suggested [24].…”
Section: Cancer Prognosismentioning
confidence: 99%